2021
DOI: 10.1177/1742271x21995523
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary image findings of lower limb stress fractures to aid ultrasonographic diagnoses: A systematic review and narrative synthesis

Abstract: Introduction This systematic review investigates which image appearances are most common when diagnosing lower limb stress fractures using ultrasound imaging, with the aim of outlining an image critique guideline for operators to support confident diagnoses. Method A comprehensive literature search of medical databases and handsearching was undertaken to identify relevant studies. All studies were critically examined for quality using the CASP critical appraisal tool. Results from eight studies were combined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Three studies revealed bone callus development (5/119), soft-tissue hypervascularity (13/119), and break in cortex (22/119). The review also concludes that future work on separating stress fractures from pathological involvement might help to lessen the need for plain film radiography 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies revealed bone callus development (5/119), soft-tissue hypervascularity (13/119), and break in cortex (22/119). The review also concludes that future work on separating stress fractures from pathological involvement might help to lessen the need for plain film radiography 22 .…”
Section: Resultsmentioning
confidence: 99%
“…In stress fractures, US have demonstrated more sensitivity than specificity except in trabecular stress fracture where it cannot evaluate subcortical bone 1 . US findings can also reveal different stress fractures findings along the lower limb which are otherwise invisible in plain radiographs but this requires further evaluation performed using larger multi-centre investigations on stress fractures diagnosis 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MRI cannot be used as the primary imaging technique primarily because of the increased cost and prolonged imaging time, despite its excellent sensitivity and specificity. 5,18 Although radiography is used as the diagnostic gold standard for detecting skeletal fractures, it does have certain limitations. Radiography employs low-dose ionizing radiation which may be contraindicated for some patients.…”
mentioning
confidence: 99%
“…Similarly, MRI cannot be used as the primary imaging technique primarily because of the increased cost and prolonged imaging time, despite its excellent sensitivity and specificity. 5,18…”
mentioning
confidence: 99%